Analysis Of The Development Of Community-Based Natural Tourism Attractions In Bukit Sawit, Girirejo Village, Ngablak District, Magelang District - Suwarti Suwarti (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Sawit Hamlet, Girirejo Village, Ngablak District, Magelang Regency In this hamlet, there is one of the community-based natural tourism attractions in the form of a Mount Andong climbing basecamp called Taruna Jaya Giri Sawit Basecamp. Together with Perhutani, the community is in charge of running this basecamp. The aim is to determine the role of the community and the factors that influence the development of community-based natural tourist attractions in Sawit Hamlet so that it can assist in developing strategies for developing these tourist attractions. This research used descriptive qualitative methods with a sample of 6 people, 1 basecamp leader, 1 basecamp member, and 4 visitors. Data from this research were obtained from interviews, observation, and documentation. Based on the research results, it can be concluded that the community plays a full role in the development of the Taruna Jaya Giri Sawit Basecamp, but their human resources have not been properly trained. Factors that influence the development of community-based natural tourism attractions in Sawit Hamlet include human resources that are not well trained, available infrastructure, and trends that are popular with tourists.